Produktivitas Perikanan Gillnet yang Berbasis di Pangkalan Pendaratan Ikan Binuangeun - Saepul Bahri; Adi Susanto; Hery Sutrawan Nurdin (JURNAL PERIKANAN DAN KELAUTAN, 2023)
One of the dominant fishing gears at the Binuangeun Fish Landing Place (PPI) is the gillnet. The aim of this research is to determine the productivity of gillnet based at PPI Binuangeun. Data collection was carried out in January-February 2023 at PPI Binuangeun, Muara Village, Wanasalam District, Lebak Regency, Banten Province. The surveys, interviews and direct observation by following fishing operations was conducted for 30 trips. The productivity of gillnets based at PPI Binuangeun is 5.78 per trip, while for millennium gillnets it reaches 9.18 kg per trip. The catch obtained was dominated by the main target catch in the form of false trevally, mackerel, Indo-Pacific king mackerel and mackerel tuna with a weight proportion reaching 89%.